Kajian feminisme dan gender: Perjuangan pustakawan perempuan dalam pengembangan perpustakaan - Rizki Putri Arbi Sari (IJAL (Indonesian Journal of Academic Librarianship), 2022)
The concept of librarianship is an important concept that must be understood to discuss women librarians and various issues about libraries. The librarian profession is very characterized when done by women. Because of the thoroughness, patience, tenacity to perform services. This understanding is important when conducting an analysis to understand the issues of social injustice that befall women in the library. Therefore, defining gender is not as a socially and culturally constructed characteristic of men and women. The cause of injustice against librarians is the understanding of stereotypes. Feminism in addition to the movement can also be seen as a point of view or analysis of the existence of women in patterns in society. On the other hand, not all women librarians are women, and I agree that some women realize the importance of working as women librarians and themselves.